A global view of protein expression in human cells, tissues, and organs - Fredrik Pontén; Marcus Gry; Linn Fagerberg; Emma Lundberg; Anna Asplund; Lisa Berglund; Per Oksvold; Erik Björling; Sophia Hober; Caroline Kampf; Sanjay Navani; Peter Nilsson; et al. (Molecular Systems Biology)
Abstract Defining the protein profiles of tissues and organs is critical to understanding the unique characteristics of the various cell types in the human body. In this study, we report on an anatomically comprehensive analysis of 4842 protein profiles in 48 human tissues and 45 human cell lines. A detailed analysis of over 2 million manually annotated, high‐resolution, immunohistochemistry‐based images showed a high fraction (>65%) of expressed proteins in most cells and tissues, with very few proteins (<2%) detected in any single cell type. Similarly, confocal microscopy in three human cell lines detected expression of more than 70% of the analyzed proteins. Despite this ubiquitous expression, hierarchical clustering analysis, based on global protein expression patterns, shows that the analyzed cells can be still subdivided into groups according to the current concepts of histology and cellular differentiation. This study suggests that tissue specificity is achieved by precise regulation of protein levels in space and time, and that different tissues in the body acquire their unique characteristics by controlling not which proteins are expressed but how much of each is produced.